2012
DOI: 10.1155/2012/427358
|View full text |Cite
|
Sign up to set email alerts
|

Few Associations Found between Mold and Other Allergen Concentrations in the Home versus Skin Sensitivity from Children with Asthma after Hurricane Katrina in the Head-Off Environmental Asthma in Louisiana Study

Abstract: Mold and other allergen exposures exacerbate asthma symptoms in sensitized individuals. We evaluated allergen concentrations, skin test sensitivities, and asthma morbidity for 182 children, aged 4–12 years, with moderate to severe asthma, enrolled 18 months after Katrina, from the city of New Orleans and the surrounding parishes that were impacted by the storm, into the Head-off Environmental Asthma in Louisiana (HEAL) observational study. Dust (indoor) and air (indoor and outdoor) samples were collected at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Several studies assessed the allergen content of the homes in that area. Some studies were done 1-2 months after the hurricanes [18,19], and some studies were done several months later, while cleanup and remediation efforts had already begun [20][21][22]. While all these articles agree that wet conditions provided an ideal environment for mold and bacterial growth with subsequent potential health effects, only in the articles that evaluated the affected area 1-2 months after the hurricanes [18,19] was the concentration of indoor mold found to be significantly higher than the mean concentration outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessed the allergen content of the homes in that area. Some studies were done 1-2 months after the hurricanes [18,19], and some studies were done several months later, while cleanup and remediation efforts had already begun [20][21][22]. While all these articles agree that wet conditions provided an ideal environment for mold and bacterial growth with subsequent potential health effects, only in the articles that evaluated the affected area 1-2 months after the hurricanes [18,19] was the concentration of indoor mold found to be significantly higher than the mean concentration outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Results from home assessments and a successful environmental asthma counselor intervention are reported elsewhere and are summarized in the following paragraph. [7][8][9] HEAL demonstrated that an evidencebased environmental asthma counselor intervention can be implemented in a postdisaster setting to improve asthma management and assess environmental exposures. We used a novel combination of the efficacious National Cooperative Inner-City Asthma Consortium (NCICAS) asthma counselor intervention 10 and the Inner-City Asthma Study (ICAS) environmental intervention 11 to intervene on 182 participants enrolled in the HEAL Study.…”
mentioning
confidence: 99%
“…7 In fact, 94% of HEAL families had moved at least once since Katrina, 68% had initiated renovations that continued during the study, and 47% had completed home renovations before enrollment. 9 In this article, we describe our experience applying CBPR principles in conducting the study, assess their utility in the context of specific strategies we employed, and thereby provide an important perspective for future environmental public health studies conducted in postdisaster communities. Our experience in conducting the HEAL Study was predicated on tenets similar to those of Lurie et al 5 To our knowledge, no comprehensive assessment has been conducted to systematically examine the utility of specific CBPR principles in a postdisaster context, especially in health-disparate, disaster-prone communities served by a fragile health system.…”
mentioning
confidence: 99%
“…The Head‐off Environmental Asthma in Louisiana (HEAL) Project, which studied the environmental impact of disaster in children with asthma living in New Orleans, is an example of collaborative research that crossed many agencies, disciplines and universities (Grimsley et al. ).…”
Section: Seize the Opportunitymentioning
confidence: 99%
“…New collaborations within the local academic environment were forged as well, as professionals across universities and disciplines partnered, capitalizing on the strengths of diverse disciplines. The Head-off Environmental Asthma in Louisiana (HEAL) Project, which studied the environmental impact of disaster in children with asthma living in New Orleans, is an example of collaborative research that crossed many agencies, disciplines and universities (Grimsley et al 2012). the more unique are the challenges of disaster research'.…”
Section: Seize the Opportunitymentioning
confidence: 99%